The history of the teaching of history: a unestable school knowledge - Mireya Gonzalez Lara (Corporación Universitaria Minuto de Dios, 2012)
The history of teaching of history in Colombia has traditionally been articulated to the path that has marked the formalization of history as an academic university field, setting his teaching as a dependent exercise, subordinated and in always in debt with the progress from research. The relatively recent emergence of the field of research in the history of school knowledge in Colombia, has been constituted in a chance to inquire about the history of the teaching of history from other theoretical and methodological references, in addition to enhance the category of "pedagogical knowledge ", and allows the exploration of other discourses that have historically shaped this knowledge, associated with teacher training, public policy, school textbooks and research on this field. This article, drawing on the situation of the Bicentennial, attempts to show this theoretical perspective and some initial sketches of the forms it has taken the teaching of history throughout the twentieth century and the first decade of the century.